Pengaruh Penerapan Intervensi Keperawatan Berupa Senam Kaki Diabetik Terhadap Pencegahan Ulkus Kaki Diabetik Pada Pasien Diabetes Melitus Tipe II Di Wilayah Kerja Puskesmas Kelurahan Lenteng Agung 2: The Effect of Implementing a Nursing Intervention in the Form of Diabetic Foot Exercises on the Prevention of Diabetic Foot Ulcers in Patients with Type II Diabetes Mellitus in the Working Area of ​​the Lenteng Agung 2 Urban Village Community Health Center - Claudia Pietersz; Yeni Kotto; Agus Purnama (MPI Press, 2026)
Introduction: Diabetes mellitus (DM) is a group of metabolic disorders characterized by elevated blood sugar levels, or hyperglycemia. Prolonged hyperglycemia can lead to various complications, one of which is diabetic foot ulcers. Diabetic ulcers occur due to impaired peripheral blood flow and nerve damage, reducing the supply of oxygen and nutrients to the foot tissue, leading to tissue damage. One preventative measure is diabetic foot exercises, simple exercises aimed at improving blood circulation, maintaining nerve function, and preventing foot ulcers. Method: This study used a quantitative method with a pre-test and post-test design. Results: showed that most respondents were in the late elderly age group (56–65 years) and the majority were female. The average random blood sugar (GDS) level before the intervention was 314.20 mg/dL, indicating uncontrolled hyperglycemia. Furthermore, screening results using the Inlow's 60-Second Diabetic Foot Screening Tool showed an average score of 8.12, which is categorized as a moderate to high risk for diabetic foot ulcers. After two weeks of regular diabetic foot exercises, the average GDS decreased to 286.84 mg/dL and the foot screening score decreased to 6.04. This indicates improvements in foot condition, particularly in circulation and sensation. Conclusion: Therefore, diabetic foot exercises can be recommended as a preventative measure for diabetic foot ulcers, which can be performed independently by patients as recommended by healthcare professionals.